Activity of Mecillinam and Clavulanic Acid on ESBL Producing and Non- ESBL Producing Escherichia Coli Isolated From UTI Cases - Shadia, Khandaker; Ahmed, Abdullah Akhtar; Barai, Lovely; Rahman, Fahmida; Tahmina, Nusrat; Haq, J Ashraful (Ibrahim Medical College Journal, 2016)
Mecillinam is one of the very few oral antibacterial agents used against extended spectrum ?- lactamase (ESBL) producing Escherichia coli (E. coli) causing urinary tract infection (UTI)). It is reported that, resistance to mecillinam can be reversed to some extent by adding beta lactamase inhibitor like clavulanic acid. The present study was aimed to determine in-vitro activity of mecillinam and mecillinam-clavulanic acid combination on the susceptibility of ESBL producing and non-ESBL producing E. coli. Total 124 E. coli (78 ESBL positive and 46 ESBL negative) isolates from urine samples of patients with UTI were included in the study. Organisms were isolated from patients attending BIRDEM General Hospital from July 2012 to December 2012. ESBL production was tested by double disc synergy test. Minimum inhibitory concentration (MIC) of mecillinam and clavulanic acid against E. coli was determined by agar dilution method. Of the total E. coli isolates, 62.9% was ESBL positive and 37.1% was negative for ESBL. Out of ESBL positive isolates, 75.6% was sensitive to mecillinam while ESBL negative isolates showed the sensitivity as 67.4%. The sensitivity to mecillinam of ESBL positive and negative isolates increased to 85.9% and 86.9% respectively by addition of clavulanic acid with mecillinam. The MIC values of intermediate and resistant isolates converted to sensitive MIC range after addition of clavulanic acid with mecillinam. Conversion of resistance of ESBL producing isolates by adding clavulanic acid was also evident by the reduction of MIC50 and MIC90 from 4?g/ml to ?1 ?g/ml and from 128 ?g/ ml to 64 ?g/ml respectively. Similar trend of reduction of MICs was also observed in non-ESBLs. In conclusion, both ESBL positive and negative E. coli demonstrated considerable sensitivity to mecillinam and the sensitivity increased significantly (p<0.05) by adding clavulanic acid with mecillinam. Ibrahim Med. Coll. J. 2014; 8(2): 56-60